THE SKULL AND LOWER JAW OF THE HOLOTYPE OF MEGALANCOSAURUS PREONENSIS (DIAPSIDA, DREPANOSAURIDAE) FROM THE UPPER TRIASSIC OF NORTHERN ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2005)
The skull of the holotype of the Late Triassic diapsid reptile Megalancosaurus preonensis is described for the first time. Its study revealed affinities with archosauromorph reptiles along with striking similarities with basal pterosaurs, apart for the absence of an antorbital fenestra.